1989
DOI: 10.1073/pnas.86.10.3753
|View full text |Cite
|
Sign up to set email alerts
|

Loss of heterozygosity for the short arm of chromosome 1 in human neuroblastomas: correlation with N-myc amplification.

Abstract: Partial monosomy of the short arm of chromosome 1 is the most consistent cytogenetic abnormality found in human neuroblastomas, but its overall frequency and significance are unclear. Using a panel of chromosome-1-specific DNA probes that identify restriction fragment length polymorphisms, we demonstrate that 13 of 47 human neuroblastomas (28%) have somatic loss of heterozygosity (LOH) at one or more loci on the distal short arm of chromosome 1. The chromosomal region that shows LOH most consistently is betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
167
3
7

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(188 citation statements)
references
References 51 publications
11
167
3
7
Order By: Relevance
“…This gene encodes the beta subunit of the barbed-end actin binding protein that regulates growth of the actin filament by capping the barbed end of growing actin filaments. Those investigators mapped the CAPZB gene to 1p36.1, which has frequent loss of heterozygosity observed in neuroblastomas (Fong et al, 1989) and in oropharyngeal epithelial carcinomas (Grati et al, 2000). Jullien-Flores et al (1995) obtained a cDNA encoding RALBP1, which they termed RLIP76.…”
Section: Discussionmentioning
confidence: 99%
“…This gene encodes the beta subunit of the barbed-end actin binding protein that regulates growth of the actin filament by capping the barbed end of growing actin filaments. Those investigators mapped the CAPZB gene to 1p36.1, which has frequent loss of heterozygosity observed in neuroblastomas (Fong et al, 1989) and in oropharyngeal epithelial carcinomas (Grati et al, 2000). Jullien-Flores et al (1995) obtained a cDNA encoding RALBP1, which they termed RLIP76.…”
Section: Discussionmentioning
confidence: 99%
“…Losses of 1p have been correlated with advanced stages and poor prognosis in some studies 3,21,54,57 and larger losses are associated with MYCN amplification. 14,15,52,58 Other investigators however have not identified an association between LOH and MYCN amplification 21 or prognosis. 58 For local-regional tumors and stage 4S, the data are less clear, although some groups have correlated 1p LOH with poor prognosis in low-risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…14,15,52,58 Other investigators however have not identified an association between LOH and MYCN amplification 21 or prognosis. 58 For local-regional tumors and stage 4S, the data are less clear, although some groups have correlated 1p LOH with poor prognosis in low-risk groups. 2 In the present study composed of cases consistently treated at a single institution, LOH of 1p36 and 1p22 was associated with stage and MYCN amplification and LOH of 1p36 was associated with survival (See Tables 1 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…These tumors account for 15% of childhood cancer deaths and are particularly noted for a wide range in clinical behavior, ranging from spontaneous regression to rapid progression and death owing to disease (Brodeur, 2003). Loss of chromosome 1p material, occurring predominately through an unbalanced t(1;17) that also results in gain of 17q (Van Roy et al, 1994), is a common chromosomal imbalance found in NB and occurs preferentially in tumors with MYCN amplification (MNA) (Fong et al, 1989). All three of these nonrandom genetic abnormalities, loss of 1p, gain of 17q and MNA, are independently associated with a poor clinical outcome (Brodeur et al, 1984;Spitz et al, 2003;Attiyeh et al, 2005;Vandesompele et al, 2005).…”
mentioning
confidence: 99%